Two-dimensional polynomial eigenstrain formulation of boundary integral equation with numerical verification - 马杭 郭钊 秦庆华 (Applied mathematics and mechanics, 2011)
The low-order polynomial-distributed eigenstrain formulation of the boundary integral equation （BIE） and the corresponding definition of the Eshelby tensors are proposed for the elliptical inhomogeneities in two-dimensional elastic media. Taking the results of the traditional subdomain boundary element method （BEM） as the control, the effectiveness of the present algorithm is verified for the elastic media with a single elliptical inhomogeneity. With the present computational model and algorithm, significant improvements are achieved in terms of the efficiency as compared with the traditional BEM and the accuracy as compared with the constant eigenstrain formulation of the BIE.